THE ROLE OF ENGLISH VARIETIES AND ACCENTS IN EFFECTIVE COMMUNICATION ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article emphasizes the importance of engaging with diverse Englishvarieties and accents to enhance communication skills, promote cultural understanding, and foster inclusivity. It explores how accents reflect the rich histories and identities oftheir speakers, highlighting examples from British, American, Australian, Caribbean, andAsian Englishes. The piece provides practical tips for improving listening skills, such asconsuming global media, practicing active listening, and engaging in conversations withspeakers from various linguistic backgrounds. The conclusion reinforces the value ofembracing linguistic diversity as a pathway to mutual respect and global connection. Through this perspective, the article underscores that language is not just a tool forcommunication but also a celebration of humanity's